Innovative Behavior in Elementary School Teachers - Umi Anugerah Izzati; Warih Handayaningrum; Olievia Prabandini Mulyana (Studies in Learning and Teaching, 2023)
Elementary school teachers have an important role in educational institutions. One of these roles is that the teacher can display innovative behavior in order to support the achievement of school goals. This study aims to analyze the description of innovative behavior in elementary school teachers. This study used a descriptive qualitative method with 12 teachers who worked in an elementary school as respondents. Data collection used unstructured interviews, and the research instrument was an interview guide. The research instrument was developed by the research team using innovative behavior theory from Jong and Hartog (2010). Data were analyzed using three processes, namely data reduction, data display and drawing conclusions. The results of this study indicate that overall, the innovative behavior of elementary school teachers is in the good category. This research is different from research that has been done by other researchers before. During this time other studies have addressed innovative behavior in employees in various corporate settings. However, to the knowledge of researchers, no one has highlighted innovative behavior in teachers at the earliest education level, namely elementary school.